Imaging Profile of Intracranial Tumors at Dr. Zainoel Abidin Regional General Hospital Banda Aceh - Bintang, Khairunnisa Setia; Novirianthy, Rima; Hidayaturrahmi, Hidayaturrahmi (Indonesian Journal of Cancer, 2024)
Background: Brain tumors are divided into two, primary and secondary brain tumors. Primary brain tumors are brain tumors that originate from the brain cells themselves. Meanwhile, secondary brain tumors are tumors that metastasize from tumors located in other parts of the body. Intracranial tumors require imaging modalities to make a diagnosis. Imaging examinations can reveal the type of tumor, location of the tumor, number of lesions, and some radiological features. However, information on imaging examination data of intracranial tumor patients is still limited, especially in Aceh, Indonesia. This study aims to determine the imaging profile of intracranial tumor patients at Dr Zainoel Abidin Regional General Hospital Banda Aceh. Methods: This study design was retrospective descriptive quantitative with the total sampling method. This study was conducted by observing all medical records of intracranial tumor patients recorded from January to December 2022 at Dr. Zainoel Abidin Regional General Hospital Banda Aceh. Results: A total of 88.5% (n=92) of the 104 registered cases were primary intracranial tumors. The most common patient profile was found to be in the range of 46-55 years (25%) and the majority was female (64.4%). The most common type of imaging used was contrast computed tomography (CT)-scan (38.5%), the most common location was supratentorial (74%), the most number of lesions was solitary (83.7%), the most common radiological picture was perifocal edema (66.3%), and the least radiological picture was communicating hydrocephalus (1.9%) and meningeal enhancement (1.9%). Conclusions:  There were more patients with primary intracranial tumors than with secondary intracranial tumors. CT scan was the most used imaging to diagnose intracranial tumors. The most intracranial tumors are supratentorial and solitary lesions with perifocal edema as common radiology features. dalities